Gamelia bennetti sp. nov., a new Saturniidae species from Trinidad and Tobago (Lepidoptera: Bombycoidea) - Cock, Matthew J.w.; Rougerie, Rodolphe (Zootaxa, 2021)
Gamelia bennetti sp. nov. is described from Trinidad, Trinidad and Tobago, West Indies, and compared with members of the Gamelia abas species group: G. abas (Cramer, [1775]), G. berliozi Lemaire, 1967, G. lichyi Lemaire, 1973, G. rubriluna (Walker, 1862) and G. septentrionalis (Bouvier, 1936). A photographic record suggests G. bennetti sp. nov. may also occur in Tobago.